2023
DOI: 10.3390/jcm12072689
|View full text |Cite
|
Sign up to set email alerts
|

Surrogates of Muscle Mass on Cardiac MRI Correlate with Exercise Capacity in Patients with Fontan Circulation

Abstract: Background: Sarcopenia is an increasingly recognized marker of frailty in cardiac patients. Patients with a history of congenital heart disease and Fontan procedure have a higher risk of developing progressive muscle wasting. Our objective was to determine if we could use routine cardiac MRI (CMR) for the surveillance of muscle wasting. Methods: A retrospective study of all Fontan patients (n = 75) was conducted at our institution, with CMR performed from 2010 to 2022 and exercise stress testing performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Smith et al reported a positive correlation between MRI-derived skeletal muscle area at (Th4) and VO 2 peak in TCPC patients [ 16 ]. However, their method of segmentation of the pectoralis major and spinal extensors is not adequately described; therefore, the repeatability of the study results is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al reported a positive correlation between MRI-derived skeletal muscle area at (Th4) and VO 2 peak in TCPC patients [ 16 ]. However, their method of segmentation of the pectoralis major and spinal extensors is not adequately described; therefore, the repeatability of the study results is questionable.…”
Section: Discussionmentioning
confidence: 99%
“… 72 Medications thought to improve exercise capacity and quality of life may be confounded by both increased frailty within ACHD patients and discordant self-estimation of FC. 73 , 74 , 75 …”
Section: Managementmentioning
confidence: 99%